Successful collaboration in online learning through skills and community building: a women in leadership MBA subject case study (Journal of Applied Learning and Teaching, 2022)
Harasim’s Collaborativism and Garrison’s Community of Inquiry are underpinned by the notion that successful online peer-peer collaboration leads to deep learning and that online learners require scaffolded facilitator support to successfully collaborate. This support includes two actions: firstly, transitioning students from the roles of face-to-face learners to online learners so they know what to do and how to do it in a new learning environment and secondly, building a strong online community that sets the positive cognitive and behavioural building blocks that underpin successful collaboration. Collaborativism sees learners progressing through distinct discourse-focussed collaboration stages in order to achieve new, deep knowledge acquisition and Community of Inquiry proposes the convergence of Social Presence, Teaching Presence, and Cognitive Presence to achieve the same. Linking theory to practice, Salmon’s 5-Stage Model for Online Learning complements these frameworks by providing facilitators with a practical online learning model, with embedded learning activities, providing the tools to create a strong online learner community. These three theorists bring Social Constructivism to the online learning space.MBA661 Gendered Workplace Environments v1, is a higher education subject, placed at an Australian Qualifications Framework level 9 (AQF-9), and at a Master of Business Administration level 600 (MBA-600). It sits within a Women in Leadership specialisation stream. It is used here in an illustrative case study on how to successfully apply these theories and aligned model to achieve online Social Constructivism. The educational philosophy used in its syllabus design and facilitation was to put community building activities before content teaching so that technology and collaboration skills were developed in a supportive, scaffolded manner, better equipping students to then engage in effective, collaborative content learning. This case study provides presumptive evidence that placing community building activities before content teaching within weekly lesson plans results in strong student collaboration skills development that may contribute to higher student satisfaction levels with collaborative learning.